Too much sitting - A health hazard - Dunstan, D.; Howard, B.; Healy, Genevieve; Owen, N. (2012)
In contemporary society, prolonged sitting has been engineered into our lives across many settings, including transportation, the workplace, and the home. There is new evidence that too much sitting (also known as sedentary behavior - which involves very low energy expenditure, such as television viewing and desk-bound work) is adversely associated with health outcomes, including cardio-metabolic risk biomarkers, type 2 diabetes and premature mortality. Importantly, these detrimental associations remain even after accounting for time spent in leisure time physical activity. We describe recent evidence from epidemiological and experimental studies that makes a persuasive case that too much sitting should now be considered an important stand-alone component of the physical activity and health equation, particularly in relation to diabetes and cardiovascular risk. We highlight directions for further research and consider some of the practical implications of focusing on too much sitting as a modifiable health risk.